The Influence Of Leadership Style, Employee Engagement, And Organizational Culture On Job Performance In The Service Industry - Manap, Abdul; Damsir (Journal Management & Economics Review (JUMPER), 2025)
organizational culture on job performance in the service industry. With the increasing importance of human capital in service-based businesses, understanding the drivers of job performance has become crucial for maintaining competitiveness and sustainability. A quantitative research approach was employed, collecting data through structured questionnaires from 210 employees working in various service organizations. The data were analyzed using multiple regression analysis to examine the relationships between the independent variables and job performance. The results revealed that leadership style, employee engagement, and organizational culture each have a significant and positive effect on job performance. Transformational leadership emerged as the most influential factor, followed by employee engagement and organizational culture. These findings suggest that service organizations should focus on developing effective leadership, fostering high levels of employee engagement, and nurturing a strong organizational culture to enhance overall job performance. The study contributes to the growing body of literature in organizational behavior and human resource management, offering both theoretical implications and practical recommendations for management in the service industry.